Implementation of Lifelong Learning Policies in South Korea: A World Society Perspective4 - Jung Eun Lee (Adult Education Research Conference, 2010)
This study examines the process of the implementation of lifelong learning policies in South Korea, and builds on a world society perspective, which views international organizations as major agents that diffuse the norm of lifelong learning across nations. Analysis of literature reveals that UNESCO through international conference on adult education (CONFINTEA) played a decisive role in South Korea’s adaptation of lifelong learning as a national agenda.